KEBERLANJUTAN LEMBAGA KEUANGAN MIKRO NON FORMALDALAM PEMBIAYAAN USAHA MIKRO RUMAH TANGGA MISKIN - Gatot Sugeng Purwono; Agustin HP (STIE Mandala Jember, 2016)
The existence of Microfinance Institutions (MFIs) non-formal become thefoundation of micro-entrepreneurs of poor households in the middle of thelimitations of access to formal financial institutions . To develop the capacity ofbusiness , micro financing for poor households served many non-formal MFIs . Thequestion is; the extent of non -formal MFIs serve as an alternative source offinancing for the development of micro poor households?, and extent of non-formalMFIs can be formulated and recommended for the development of micro poorhouseholds?. The study was conducted in the District of Jember Kencong targetingnon-formal MFIs and micro entrepreneurs poor household member non-formal MFIs. This study is the first year of a two year study is planned. The objective inventory ofnon-formal MFIs effectively and sustainably manage savings and loans potentiallyserve microenterprises poor households. Descriptive analysis, MFIs independentlyconstructed by society more sustainable potential compared with other partiesinitiated by the government for example .